Effectiveness Of Using Video Tutorials To Improve Online Learning In Pandemics - Gina Tuty Alawiyah; Putri Banyu Suryani; Yusya Nur Salam; Siti Sahronih (Al-Makki Publisher, 2022)
This study aims to examine the use of video tutorials on the effectiveness of online learning during the pandemic. This research method uses qualitative research that is library research taken from several journals with data collection techniques using literature studies, namely reviewing various written sources in previous research articles. The results of this study conclude that the use of video tutorials contributes and influences in making online learning effective during the pandemic which can be applied in one of the subjects in elementary school, for example, mathematics. The low level of online learning is due to the low performance of teachers in the boring learning process and not using creative media.